2020
DOI: 10.9734/aprj/2020/v6i130118
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Polyphenols and Carotenoids Extraction from Leaves of Cassia auriculata for Natural Health Products

Abstract: Aims: C. auriculata leaves contains polyphenols and carotenoids and also it posses various antioxidant activities towards free radical scavenging, lipid peroxidation inhibition and reducing potential. The present study investigated the optimization of polyphenols and carotenoids extraction from Cassia auriculata leaves by response surface methodology (RSM). Study Design: A three-factor, three-levels central composite design (CCD) was performed to determine the effect of solvent concentration (30-100%), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…The study found that increasing the extraction temperature from 40 to 70 °C led to a significant increase in GA concentration. This observation is consistent with other research that has shown an increase in the recovery of phenolic compounds with the increase in extraction temperature, up to a certain point 74 . Higher extraction temperatures enhance solubility, diffusion rate, mass transfer rate, and surface tension, which improve the extractability of phenolic compounds 75 .…”
Section: Discussionsupporting
confidence: 93%
“…The study found that increasing the extraction temperature from 40 to 70 °C led to a significant increase in GA concentration. This observation is consistent with other research that has shown an increase in the recovery of phenolic compounds with the increase in extraction temperature, up to a certain point 74 . Higher extraction temperatures enhance solubility, diffusion rate, mass transfer rate, and surface tension, which improve the extractability of phenolic compounds 75 .…”
Section: Discussionsupporting
confidence: 93%